PENERAPAN METODE NARASI ARSITEKTUR DALAM PERANCANGAN EKSTRAKURIKULER PENDIDIKAN EKOLOGI DI KAWASAN EDUTOWN, BSD - Ferdi James; Fermanto Lianto (Jurusan Arsitektur dan Perencanaan, 2021)
Life in urban areas, which is accelerating and capitalist, makes humans less sensitive to their environment. Students only learn about nature and the environment through literacy and lack opportunities to learn directly from nature in urban areas. It causes a lack of awareness and mindset and indifferent behaviour towards nature and the surrounding environment within the city. With all the acceleration of development, BSD City must be balanced with the behavioural pattern of people who are aware and care about the environment. This project is a preventive measure against environmental damage. Technology and materials must be sustainable and environmentally friendly, but what is fundamental is human behaviour that must be sustainable and friendly to the environment and nature. Therefore, through the program